Radiocarbon dating of aeolianite formation - Monge-Soares, A.M. (2020)
Several consolidated carbonate -rich sand dunes (aeolianites) of Late Pleistocene age are known along western and southern Portuguese coasts. Marine transgressions and regressions allowed the onshore deposition of carbonate -rich sands. The subsequent aeolian reworking is in the origin of the aeolianites, which usually occur at similar geomorphologic positions. If it is postulated that the carbonate -rich sand that is deflated from a coastal dune field to form aeolianites had an apparent radiocarbon age that is characteristic of that dune field at the time when the deflation occurred, then the radiocarbon dates obtained from samples collected at aeolianites from a same region will indicate its relative chronology. At Praia Azul, S. Julião, Samarra, Magoito, Aguda, Praia das Maçãs and Oitavos, all located in the Portuguese Estremadura, some of these aeolian sand deposits can be observed. For two of them, Magoito and Oitavos, reliable dates for their formation were determined, since a epipaleolithic midden and a paleosol, respectively, exist at the base of the aeolianites. Magoito has a Holocene age, probably formed during the Pre -Boreal period, whilst the Oitavos aeolianite was probably generated during the last interstadial of OIS 3 (ca.32000 BP). Samples from Magoito and Oitavos, and also from S. Julião, Aguda and Praia Azul aeolianites were collected in order to determine their relative and, if possible, also their absolute chronologies. Aguda and Magoito aeolianites have the same apparent age (ca. 20000 BP), suggesting that Aguda is also of Holocene age. Samples collected at different places at S. Julião have the same apparent age suggesting that only one aeolianite generation is present. This apparent age is the same determined for Oitavos aeolianite suggesting that both were formed during the last interstadial of OIS 3. Praia Azul aeolianite has the youngest apparent age, only differing one thousand years from the apparent age of the Praia Azul present-day dune field. This research allowed to prove that radiocarbon dating of the aeolianite carbonate fraction is a successful tool not only to test contemporaneity of aeolianite formation but also to set up a geochronologic framework where to place consolidated aeolian carbonate -rich sand deposits from a given region.